Increasing Farmers’ Productivity in Critical Land in Lokapaksa Village in Bali Through The Application of Water Harvesting Technology and Hydrams Towards a Green Economy - Rahmawati, Putu Indah; Dantes, Gede Rasben; Putra, I Gusti Agung Ngurah Surya (PT Inovasi Pratama Internasional, 2025)
Buleleng Regency, in Bali, is one of the areas with the longest drought in 2023. The use of water for tourism also has an impact on farmers, some water sources have dried up. Critical and barren land, in addition to being difficult to cultivate into agricultural land and plantations, is also prone to fire hazards and is a factor causing poverty. The purpose of this research is to increase the productivity of farmers on critical land by using simple technology of water harvesting and hydraulic pumps towards a Green Economy. The implementation of service was carried out in Lokapaksa by involving the participation of the village community. This service program that has been implemented is in the form of the application of simple technology for water harvesting and empowerment of village communities through the installation of hydram pumps and the planting of moringa and duren trees. The output produced from this community service project is a KEREN agro-edutourism pilot garden as an effort to realize an example of sustainable tourism and green economy.